Can the COVID-19 Crisis be a Catalyst for Transition to Sustainable Urban Mobility? Assessment of the Medium- and Longer-Term Impact of the COVID-19 Crisis on Mobility in Brussels - Macharis, Cathy; Tori, Sara; de Séjournet, Alice; Keseru, Imre; Vanhaverbeke, Lieselot (Frontiers in Sustainability, 2021)
In this paper, we investigate what the impact of the COVID-19 crisis was on travel patterns and how it could be a catalyst for the transition towards a more sustainable mobility system. To study this, we use the sustainable mobility framework of the 7A’s, namely Awareness, Avoidance, Act and Shift, Anticipation of new technologies, Actor involvement, Acceleration, and Adaptation of behavior. For each of the first 5 A’s, we analyze the changes in mobility brought along in the different periods of the COVID-19 crisis. Our mixed methods approach includes a thematic analysis of online press articles and an analysis of traffic and passenger volume data in Brussels, Belgium. Our results show that the measures to stop the spread of the COVID-19 virus had significant consequences for mobility in Brussels by raising Awareness of the positive impacts reduced traffic can have on livability. The measures decreased travel demand (Avoidance) in general, but especially in the context of commuting and shopping trips which declined in favor of telework and online shopping. The majority of mobility measures that were implemented belong to the Act and shift category and they were especially aimed at promoting active mobility like walking. There was also a positive influence on the Anticipation of new technologies, as internal combustion engine sales dropped and electric vehicle sales increased. However, the data analysis also shows an incremental return to business-as-usual after the 2020 summer holidays. Parts of this can be linked back to a disregard of Actor involvement, resulting in a resistance from stakeholders to several of the measures. We conclude with recommendations based on Acceleration and Adaptation of behavior on how to support a sustainable transition and lasting behavioral change in the post-COVID era.